Pengaruh Motivasi Belajar dan Dukungan Sosial terhadap Self Regulated Learning di SMK Rosma Karawang: Penelitian - Randwitya Ayu Ganis Hemasti; Nur Ainy Sadijah; Fatima Azzahra; Khansa Khoirunnisa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
High school students in their developmental stage are classified as adolescents. Today's adolescents face a lot of pressure, starting from environmental and socio-cultural conditions as well as their own personal development. This study aims to determine the effect of learning motivation and social support on Self-Regulated Learning at SMK Rosma Karawang. The data method in this study uses a quantitative method. The number of samples used was 182 students at SMK Rosma Karawang using a simple random sampling method. The scales used in this study were the self-regulated learning scale, the learning motivation scale, and the social support scale. The results of this study indicate that a significance value of 0.000, which means that learning motivation and social support have a positive influence on self-regulated learning in SMK Rosma Karawang students. Social support and learning motivation each have an influence of 2.4% and 2.91% on self-regulated learning, respectively. This study shows that the higher the learning motivation and social support a student has, the higher the level of self-regulated learning of the student.